Identification of a Soft Coral Garden Candidate Vulnerable Marine Ecosystem (VME) Using Video Imagery, Davis Strait, West Greenland - Long, Stephen; Sparrow-Scinocca, Bridget; Blicher, Martin E.; Hammeken Arboe, Nanette; Fuhrmann, Mona; Kemp, Kirsty M.; Nygaard, Rasmus; Zinglersen, Karl; Yesson, Chris (Frontiers in Marine Science, 2020)
The term vulnerable marine ecosystems (VMEs) was introduced to facilitate the spatial management of deep-seas, identifying those habitats vulnerable to anthropogenic disturbance, such as trawling. Consistent interpretation of the VME definition has been hampered by a underlying paucity of knowledge about the nature and distribution of deep-sea habitats. Photographic and video platforms yield data rich, quantifiable imagery to address these knowledge gaps. A low-cost towed benthic video sled has been used to investigate deep-sea habitats and trawling impacts in west Greenland. A review of imagery from multiple cruises highlighted an area where benthic megafauna contributes to notable structural complexity on the continental slope of the Toqqusaq Bank. Quantitative analysis of imagery from this area provides the first description of a soft coral garden habitat and other communities. The coral garden and observed densities are considered in relation to the VME guidelines (FAO, 2009) and wider literature. The study proposes a 486 km2 area spanning ~60 km of continental slope as a VME. This has direct implications for the management of economically important deep-sea trawl fisheries, which are immediately adjacent. This furthers our knowledge and understanding of VMEs in North Atlantic, in a previously understudied region and demonstrates the utility of a low-cost video sled for identifying and describing VMEs.